COMPARISON OF MATHEMATICS LEARNING RESULT OF STUDENTS TAUGHT BY EMPLOYING SCIENTIFIC APPROACH, PROBLEM POSING, AND OPEN ENDED IN PROBLEM BASED LEARNING MODEL IN CLASS X AT SMAN 2 MAKALE - Palengka, Inelsi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The study aimed at examining (1) the learning result of student after being taught by employing scientific approach, problem posing approach and open ended approach in problem-based learning model, (2) the differences of improvement of student’s learning result taught  by employing scientific approach, open ended approach and problem-posing approach in problem-based learning model. This study was a quasi-experiment with pretest-posttest control group design. The population of the study was class X students at SMAN 2 Makale of academic year 2014/2015 which consisted of 4 classes. Samples were selected by employing purposive sampling technique and obtained class X2 with 28 students, X3 with 23 students, and X4 with 23 students. Afterwards, the three classes were taught using scientific approach, problem posing approach, and open ended approach in problem-based learning model. The learning package used was lesson plan, student’s workbook, and student’s book. The research instruments were test of learning result, self assessment, and learning implementation. The result of the study revealed that (1) the mean score of student’s learning result using scientific approach in problem-based learning on knowledge aspect was 83.33 and attitude aspect was 90.03. Student’s who had achieved master on knowledge aspect was 84%, so the mastery learning result classically had been achieved; the attitude aspect had achieved 96% so the student’s attitude was in very good category. The mean score of student’s learning result using problem posing approach in problem-based learning model on attitude aspect was 86.95 and knowledge aspect was 70.61. Student’s who had achieved mastery was 23%, so the mastery learning result classically had been achieved; the attitude aspect had achieved 95% so the student’s was in very good category. The mean score of student’s learning result using open ended approach in problem-based learning on attitude aspect was 88.24 and knowledge aspect was 66.96. Student’s who had achieved mastery was 35%, so the mastery learning result classically had yet to achieve; the attitude aspect indicated that 100% of student’s was very good category, (2) there was significant difference of learning result of students who were taught by employing scientific approach, problem posing approach, and open ended approach